Building a Strong Organizational Culture for Sustainable Development of Tourism Companies - Marian NĂSTASE; Ileana VĂLIMĂREANU (Revista de Management Comparat International)
Successful managers in tourism services exercise their special influence through managerial and organizational culture. At the same time, they help these cultures to shape and transform. In turn, organizational and managerial culture will shape the attitudes and behaviors of managers and employees in companies. The purpose of this article is to show the importance and the fact that the role of a manager is a more complex one now, he will no longer act only as a person holding the "absolute truth", making decisions to impose upon others, but will have to act as a facilitator, as a mediator who will offer the possibility of manifesting the personality, the knowledge of the employees and, on this basis, he will adopt the best course of action. The sustainable development of tourism companies depend to a large extent to the characteristics of organizational culture that is created and permanently reshaped, but also on the leadership practiced within.